-7v+7=-3(v-9)

Simple and best practice solution for -7v+7=-3(v-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7v+7=-3(v-9) equation:



-7v+7=-3(v-9)
We move all terms to the left:
-7v+7-(-3(v-9))=0
We calculate terms in parentheses: -(-3(v-9)), so:
-3(v-9)
We multiply parentheses
-3v+27
Back to the equation:
-(-3v+27)
We get rid of parentheses
-7v+3v-27+7=0
We add all the numbers together, and all the variables
-4v-20=0
We move all terms containing v to the left, all other terms to the right
-4v=20
v=20/-4
v=-5

See similar equations:

| h-32.061=-762.46 | | 10y-7=-10y-7 | | 9s+7=8s | | 7+9r=7r-7+9r | | t+33=2 | | 4v-9=2v+9 | | p+22=2 | | 6n-2(n=3) | | 3h-6=4h | | P=-8t^2+7t-9 | | 4+10t=9t | | G=3t^2-5t+6 | | 12a-4(5-1)=2(3a+6)-4a | | x-38=8+2x | | -8-2s=-s | | 3-7y=-8y | | 6^-2n=36 | | xx4=2(x+8) | | 10x+81=21x+4 | | 5x-4=+6 | | 5x+5=x-11 | | 7k+15=-55 | | 35+12y=-y^2 | | -4(-6+5x)=24+8x | | F(10)=-2x+13 | | -8=28+12m | | 2x-6+8=4x-2 | | 19x-2+16x+2=75 | | (19x-2)(16x+2)=75 | | 3w-11+85=180 | | Y=-3/2x+1/4 | | 7x+89=17x-1 |

Equations solver categories